Religious feelings in pre-school children in their own and their mothers’ perception - Tatala Małgorzata; Mańkowska Maria (Journal for Perspectives of Economic Political and Social Integration, 2015)
The aim of the study was to compare the expression of religious feelings in pre-school children and the perception of these feelings by the children’s’ mothers. Ninety Polish children from Catholic families aged 4, 5 and 6 participated in the study. A picture method along with interviews with children’s mothers were employed to gather the data. Data from the two sources was compared, taking into consideration the content and ways of expression of the described feelings. Relations between positive and negative feelings were investigated and further statistical analyses were focused mainly on negative feelings. It was found that structure of negative religious feelings obtained directly from the children bears significant similarity to the mothers’ perception.